The Role of HER2 in Self-Renewal, Invasion, and Tumorigenicity of Gastric Cancer Stem Cells - Sun, Li-Fei; Yang, Kun; Wang, Yi-Gao; Liu, Yu-Xin; Hou, Pei-Xian; Lu, Zheng-Hao; Chen, Xiao-Long; Zhang, Wei-Han; Zhou, Zong-Guang; Mo, Xian-Ming; Hu, Jian-Kun (Frontiers in Oncology, 2020)
Background Deregulation of HER2 expression could affect the biological characteristics of gastric cancer cells and treatment option for gastric cancer patients. This research aims to investigate the impact of HER2 on biological characteristics of gastric cancer stem cells (GCSCs) and prognosis of gastric cancer patients. Methods HER2 knockdown in GCSCs were constructed by lentivirus transfection. Alterations of proliferation, self-renewal, invasion, migration, colony formation, and tumorigenicity of GCSCs were examined. The changes of gene expressions after HER2 interference in GCSCs were detected by gene microarray. The impact of concentration of serum HER2 and expression of HER2 in tumor tissues on survival of 213 gastric cancer patients was also analyzed. Results Down-regulation of HER2 decreased the self-renewal, colony formation, migration, invasion, proliferation, and chemotherapy resistance of GCSCs. However, the tumorigenicity of GCSCs in vivo was increased after down-regulation of HER2. The results of gene microarray showed that HER2 gene might regulate the signal transduction of mTOR, Jak-STAT, and other signal pathways and affect the biological characteristics of GCSCs. Furthermore, survival analyses indicated that patients with high concentration of HER2 in serum had a favorable overall survival. However, there was no significant correlation between expression of HER2 in tumor tissue and overall survival. Conclusion Interference of HER2 in GCSCs decreased the capacity of self-renewal, proliferation, colony formation, chemotherapy resistance, invasion, and migration but might increase the tumorigenicity in vivo. Patients with high concentration of HER2 in serum seemed to have a favorable prognosis.